Assessing the Relationship between Software Assertions and Code Quality: An Empirical Investigation - Kudrjavets, Gunnar; Nagappan, Nachi; Ball, Thomas (2006)
The use of assertions in software development is thought to help produce quality software. Unfortunately, there is scant empirical evidence in commercial software systems for this argument to date. This paper presents an empirical case study of two commercial software components at Microsoft Corporation. The developers of these components systematically employed assertions, which allowed us to investigate the relationship between software assertions and code quality. We also compare the efficacy of assertions against that of popular bug finding techniques like source code static analysis tools. We observe from our case study that with an increase in the assertion density in a file there is a statistically significant decrease in fault density. Further, the usage of software assertions in these components found a large percentage of the faults in the bug database.